Prayer and Technology in Increasing the Effectiveness of Theological Education in the Digital Era - Deborah Pujiwati; Tri Subekti (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
This research discusses the interaction between prayer and technology in enhancing the effectiveness of theological education in the digital age. The key issues addressed in this study include the challenges of traditional theological education, the impact of technology on the teaching and learning process, and the importance of integrating spiritual practices within a digital context. The aim of this research is to explore how prayer can be integrated with technology to create a deeper and more effective learning experience. The research method used is qualitative, involving interviews with theological educators, as well as content analysis from various digital educational platforms. The state of the art in this research indicates that while technology has transformed the way education is delivered, many theological education institutions still have not optimized the potential for integrating prayer into the learning process. The novelty of this research lies in its emphasis on the relationship between spiritual practices and the use of technology, which can enhance student engagement and understanding. The findings suggest that the combination of prayer and technology can create a more interactive and supportive learning environment, as well as increase student motivation and retention in theological education. This research is expected to provide insights for theological educators in utilizing technology more effectively while maintaining the spiritual aspects of teaching.